A combined method for evaluating radon and progeny in waters and its use at Guarani aquifer, São Paulo State, Brazil - Bonotto, Daniel Marcos [UNESP]; Mello, C. B. (Elsevier B.V., 2006)
A combined method for evaluating radon (Rn-222) and progeny (Pb-214 and Bi-214) in water was developed by using inexpensive alpha scintillation Counting and gamma ray spectrometry through NaI(Tl) scintillation detectors. A groundwater sample collected at the Pocos de Caldas alkaline massif in Brazil was submitted to the technique in order to assure its applicability by comparing the volumetric activities by different methods. Similar volumetric activity was determined for Pb-214 and Bi-214 in the sample analyzed that is compatible with the expected condition of radioactive equilibrium between these nuclides. The combined method was successfully used to analyze groundwater samples from Guarani aquifer in S (a) over tildeo Paulo State, Brazil, and the results of the measurements indicated that Pb-214 and Bi-214 provide useful information concerning the evaluation of the drinking water quality in terms of radiological aspects. This is because they are directly identified in the water samples, without the need of requiring the assumption of the establishment of the transient equilibrium condition with its parent Rn-222. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: alpha scintillation counting; gamma ray spectrometry; drinking water quality; radon and progeny; Guarani aquifer